2019
DOI: 10.1016/j.neuroimage.2019.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala-prefrontal cortex white matter tracts are widespread, variable and implicated in amygdala modulation in adolescents

Abstract: The amygdala is critically involved in processing emotion. Through bidirectional connections, the prefrontal cortex (PFC) is hypothesized to influence amygdala reactivity. However, research that elucidates the nature of amygdala-PFC interactions -through mapping amygdala-prefrontal tracts, quantifying variability among tracts, and linking this variability to amygdala activation -is lacking. Using probabilistic tractography to map amygdala-prefrontal white matter connectivity in 142 adolescents, the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 67 publications
3
46
0
Order By: Relevance
“…Probabilistic tractography uses dMRI to precisely map white matter tracts between structures ( Behrens et al, 2007 ). This method, in a smaller subset of the current sample, showed that amygdala white matter connectivity with the orbitofrontal cortex (OFC – Brodmann’s Area (BA) 47, 11), dorsomedial PFC (BA10), and subgenual cingulate (BA25) was greater than amygdala white matter connectivity with other PFC regions, such as the dorsal anterior cingulate and dorsolateral PFC ( Goetschius et al, 2019 ). Non-human primate studies also provide support for specific amygdala connectivity with the OFC, dmPFC, and subgenual cingulate ( Ray and Zald, 2012 ; Zikopoulos et al, 2017 ).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Probabilistic tractography uses dMRI to precisely map white matter tracts between structures ( Behrens et al, 2007 ). This method, in a smaller subset of the current sample, showed that amygdala white matter connectivity with the orbitofrontal cortex (OFC – Brodmann’s Area (BA) 47, 11), dorsomedial PFC (BA10), and subgenual cingulate (BA25) was greater than amygdala white matter connectivity with other PFC regions, such as the dorsal anterior cingulate and dorsolateral PFC ( Goetschius et al, 2019 ). Non-human primate studies also provide support for specific amygdala connectivity with the OFC, dmPFC, and subgenual cingulate ( Ray and Zald, 2012 ; Zikopoulos et al, 2017 ).…”
Section: Introductionmentioning
confidence: 90%
“…Non-human primate studies also provide support for specific amygdala connectivity with the OFC, dmPFC, and subgenual cingulate ( Ray and Zald, 2012 ; Zikopoulos et al, 2017 ). Additionally, our previous work revealed that adolescents with less white matter connectivity between the amygdala and the OFC (right BA47, left BA11) and dmPFC (bilateral BA10), but not the dorsolateral PFC, anterior cingulate, or subgenual cingulate, showed greater amygdala activation to threatening faces ( Goetschius et al, 2019 ). Thus, the OFC, dmPFC, and subgenual cingulate seem to be well-connected via white matter to the amygdala.…”
Section: Introductionmentioning
confidence: 99%
“…The amygdala and PFC are connected both structurally and functionally 42,47‐51 and the amygdala has an inhibitory effect and can deactivate mPFC activity 42,47,52 . The reduction in connectivity between the right amygdala and DLPFC can point to a decrease in the inhibitory effect of the amygdala on the PFC that was related to the greater CBT effect.…”
Section: Discussionmentioning
confidence: 99%
“…The first principle requires a much closer alignment between human and animal research. There is a plethora of human literature on functional and structural connectivity in disordered affect (109)(110)(111)(112)(113)(114). These human neural pathways should serve as a blueprint for rodent experimentation, yet most circuit studies to-date base their hypotheses on prior rodent work.…”
Section: Sex As a Biological Variablementioning
confidence: 99%